1999
DOI: 10.1007/s004120050371
|View full text |Cite
|
Sign up to set email alerts
|

What makes homologous chromosomes find each other in meiosis? A review and an hypothesis

Abstract: The conditions re reviewed that must be met by any model of long distance attraction and transport of homologous chromosomes to the points of intimate DNA synapsis. A proposal for possible mechanisms is presented. It includes transcription and repair factors acting on coding sequences as a preparatory step toward pairing, and the attachment of specific pairing proteins to these sequences. Double-strand break formation is prepared but not immediately completed at the same sites. It is concluded that DNA-DNA int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(43 citation statements)
references
References 88 publications
1
42
0
Order By: Relevance
“…Chiasmata and crossing over are generally located in specific segments of chromosomes, and the standard is genetically controlled (Sybenga 1999). In maize (Zea mays L.), the frequency of chiasmata is under polygenic control, which may lead to genetic variability in lineages (Pagliarini 1980).…”
Section: Discussionmentioning
confidence: 99%
“…Chiasmata and crossing over are generally located in specific segments of chromosomes, and the standard is genetically controlled (Sybenga 1999). In maize (Zea mays L.), the frequency of chiasmata is under polygenic control, which may lead to genetic variability in lineages (Pagliarini 1980).…”
Section: Discussionmentioning
confidence: 99%
“…Minisatellites at imprinted loci are thought to play a role in the imprint control (Chaillet et al 1995;Neumann et al 1995). More speculatively, minisatellites have been proposed as intermediates in chromosome pairing initiation in some eukaryote genomes (Ashley 1994;Sybenga 1999), which might be related to their proposed recombinogenic properties (Boan et al 1998;Wahls and Moore 1998). (3) Finally, minisatellites may constitute chromosome fragile sites (for review, see Sutherland et al 1998) and have been found in the vicinity of a number of recurrent translocation breakpoints and in the switch recombination site in immunoglobulin heavy chain genes (Brusco et al 1999).…”
Section: Classic Definition and Early Applications Of Minisatellitesmentioning
confidence: 99%
“…Subtelomeric minisatellites are one class of sequences that have been put forward as candidates to help explain this paradox (Ashley 1994;Sybenga 1999). Specific mechanisms would be activated in male meiosis, and minisatellites would be involved in chromosome pairing, either directly or via interactions with pairing proteins.…”
Section: Genome Research 903mentioning
confidence: 99%
“…There are several recent papers on this subject, both from a cytogenetic and a mathematical modelling point of view (Sybenga, 1994(Sybenga, , 1995(Sybenga, , 1996(Sybenga, , 1999Jackson and Jackson, 1996). The evidence suggests that these situations should be characterised by a general polyploid inheritance model with no complete preference to homologous or homeologous paring (Wu et al, 2001).…”
Section: Introductionmentioning
confidence: 99%